Impact of Genital and Non-Genital Psoriasis on Genital Self-Image, Quality of Life, and Sexual Dysfunction in Female Patients - Hala M. Elsadek; Mona S. Ali; Asmaa M. Elaidy (Mattioli1885, 2024)
Introduction: Psoriasis is a chronic systemic inflammatory disease that affects millions of people worldwide. While its physical manifestations are well-documented, the psychosocial impact of psoriasis, particularly on female patients, is an area of growing concern. Feelings of shame, inferiority, and stigma are common among individuals with psoriasis, and these emotional burdens can be especially pronounced in females, particularly when the genital area is affected.  Objectives: We aimed to shed light on the significance of genital psoriasis on the  overall well-being of female patients. Methods: We conducted a cross-sectional assessment of quality of life using the Dermatology Life Quality Index (DLQI), sexual function using Female Sexual Function Index (FSFI), genital self-image using Female Genital Self-Image Assessment (FGSIS), among Egyptian females with and without genital psoriasis. By comparing these aspects across different groups, Results: We found that females with genital lesions, experience a notable decline in sexual health with higher levels of sexual distress compared to healthy individuals. In terms of the six FSFI domains, the psoriatic group scored lower than the control group in all areas, except for pain, which showed a significant increase. Psoriatic females also exhibited a significantly more negative FGSIS compared to the control group, and there was a highly significant difference in FGSIS between females with and without genital psoriasis. Conclusion: Understanding the impact of genital psoriasis on female sexual health and overall quality of life is essential for comprehensive patient care This research is instrumental in addressing the psychosocial aspects of psoriasis and enhancing patient well-being.